PERAN WORK – FAMILY BALANCE DENGAN PERHATIAN TERHADAP PENDIDIKAN ANAK PADA IBU BEKERJA - Krisnia Ken Tantri (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2021)
Today, a woman who is married and works outside is common. Married career women or working mom are faced with 2 (two) roles, first as an employee with duties and responsibilities in the office and second as a housewife with the task of taking care of the house, husband and children. With this dual role, Working Mom are expected to function in a balanced way both at work and at home. This balance is referred to as Work-Family Balance, namely the extent to which an individual is fully involved and satisfied with his role in work and his role in the family. As a mother and parent, one of the roles of a career woman is in taking care of children. Taking care of children here is not only how a mother meets the needs of children in terms of food, clothing, shelter and affection, but also in terms of education. Children entering school age need parental attention regarding their education. This study uses correlational quantitative methods with research subjects 30 working mom who have school-age children. The data collection instrument used a Likert Scale for the Work Family Balance Scale and the Attention to Children's Education Scale. Methods of data analysis using Pearson Correlation Analysis with the results of the analysis obtained a correlation coefficient of 0.384 with a significance of 0.036 (p <0.05) which means that Work Family Balance has a correlation with attention to Child Education in Working Mom, in other words the more a working mom can balancing their roles at work and at home the more attention can be paid to their child's education.Key Word : Work – Family Balance, Child Education, Working Mom